Komparasi antara Silabus Rongrien Bakong Pitayya School Pattani Thailand Selatan dengan Silabus Madrasah Ibtidaiyah - Widya Rahmawati Al-Nur (BASICA: Journal of Primary Education, 2021)
The syllabus is a mandatory component present in learning and teaching activities. Educators must prepare all kinds of needs in delivering classroom learning materials. The syllabus is part of the curriculum whose contents include RPP that is tailored to the class level and adjusts to where the RPP is made and run. Therefore, educators feel facilitated by the syllabus in preparing learning and teaching activities in every educational institution. The problem that researchers will study is how to paraphrase the syllabus in Rongrien Bakong Pittaya school with the syllabus in MI Ma'arif NU 1 Pageraji. This research is field research related to syllabus documentation in two schools. The author uses interview techniques and documentation to collect data, and the research subject is the Waka curriculum and educators. In addition to analyzing research data, researchers use cumulative descriptive methods. While the result is to show the similarity of syllabus functions in both educational institutions; namely, the syllabus becomes a handle in curriculum-oriented learning activities that have been set in accordance with the needs of each educational institution. However, it has similarities regarding the format of the syllabus between the two educational institutions, the content of the subject matter submitted, and KD.